UJI EFEKTIFITAS ANTIBAKTERI EKSTRAK KULIT BATANG JAMBU MONYET (Bellucia pentamera Naudin) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DAN Salmonella typhi - Farid Priandi; Fathul Yusro; Farah Diba; Yeni Mariani; . Nurhaida (Tengkawang : Jurnal Ilmu Kehutanan, 2019)
People still use plants as a medicine to overcome a disease, because it is easily to obtain and relatively does not provide significant negative effects. One of the plants utilized by the people is Bellucia pentamera Naudin (B. pentamera). Diarrhea and typhoid fever are diseases that often assault Indonesian people. The bacterias were used in this study were Escherichia coli (E. coli) and Salmonella typhi (S. typhi). This study aimed to analyze the antibacterial effectiveness of B. pentamera bark extracts against E. coli and S. typhi, by Kirby-Bauer diffusion method with PCA as the media. The highest extract concentration against E. coli is 400 mg/ml possess an inhibition of 20±1 mm, and towards S. typhi is 80 mg/ml which possess an inhibition of 24.67±0,58 mm.Keywords: Bellucia pentamera, Disc Diffussion, Efectiveness, Escherichia coli, Salmonella typhi.